2021
DOI: 10.33160/yam.2021.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Photodynamic Therapy Using Talaporfin Sodium for Local Failure of Esophageal Squamous Cell Carcinoma

Abstract: Background Talaporfin sodium photodynamic therapy (TS-PDT) for local failure after chemoradiotherapy (CRT) in patients with esophageal squamous cell carcinoma has recently been reported to be highly effective and less invasive, compared to other treatment modalities. TS-PDT was recently introduced at the Tottori University Hospital, Japan. The aim of this study is to clarify the efficacy and safety of PDT in our hospital. Methods This was a single-center observational study. We examined eight cases of TS-PDT p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This preliminary retrospective study found that the CCI was negatively associated with the efficacy of salvage TS-PDT for esophageal cancer. We believe that this result has Intern Med Advance Publication DOI: 10.2169/internalmedicine.1907-23 (7,(15)(16)(17)(18). According to these studies, the L-CR rate ranged from 55.6% to 88.5%, and the likelihood of an L-CR was significantly affected by the clinical invasion depth of the tumor before PDT.…”
Section: Discussionmentioning
confidence: 89%
“…This preliminary retrospective study found that the CCI was negatively associated with the efficacy of salvage TS-PDT for esophageal cancer. We believe that this result has Intern Med Advance Publication DOI: 10.2169/internalmedicine.1907-23 (7,(15)(16)(17)(18). According to these studies, the L-CR rate ranged from 55.6% to 88.5%, and the likelihood of an L-CR was significantly affected by the clinical invasion depth of the tumor before PDT.…”
Section: Discussionmentioning
confidence: 89%
“…The present patient received talaporfin sodium PDT (TS-PDT) for local recurrence after chemoradiotherapy (CRT) for esophageal cancer and achieved complete local remission. TS-PDT for local failure after CRT in patients with esophageal squamous cell carcinoma has recently been reported to be highly effective and less invasive than other treatment methods ( 11 , 12 ). However, our patient experienced lymph node metastasis approximately two years later, and nivolumab was administered.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, PDT has shown promising results in management of persistent or recurrent disease after initial treatment with chemoradiation therapy. 24,[29][30][31][32][33] In PDT, a photodynamic reaction is triggered by laser light on a photosensitizing drug that has an affinity for tumors. 46 PDT offers variable tissue penetration depending on the wavelength of the light source and the agent used.…”
Section: Pdt As Salvage For Esophageal Cancer After Crtmentioning
confidence: 99%
“…Besides surgery and endoscopic resection, other salvage treatment modalities for lesions initially treated with CRT include photodynamic therapy (PDT), 24,29-33 radiofrequency ablation, and spray cryotherapy. We will now review salvage endoscopic therapy in more detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation